“Las exportaciones, la globalización sociocultural y el crecimiento económico en el Ecuador durante el periodo 1990-2022: Un estudio de series de tiempo” - Naula Chacón, María José (2025)
Over the last decades, Ecuador's economic growth has fluctuated considerably due to financial crises, natural events, and health emergencies, with the lowest decline rate being -7.80% in 2020. Therefore, the general objective of this investigation was to examine the effect of exports, foreign direct investment, labor force participation, and sociocultural globalization on economic growth in Ecuador during the period 1990-2022. Thus, data from the World Bank and the KOF Globalization Index were used to extract and analyze the study variables, through the application of time series econometric strategies such as cointegration, short/long-term models, and causality tests. In general, changes and trends were found in the variables analyzed, and it was evident that there is a short- and long- term effect between exports, sociocultural globalization, and economic growth, whose causality differs when the Granger and Breitung-Candelon tests are applied. Based on the results, economic policy recommendations were made to boost economic growth in the country, with the promotion of exports, the implementation of contingency plans for future crises and the promotion of the tourism sector for greater cultural exchange being important.